Avaliação do risco de colapso de ecossistemas terrestres em três biomas no Brasil: Mata Atlântica, Cerrado e Caatinga - Manuel Loureiro Gontijo (2020)
Ecosystem degradation is a global problem and has been affecting environment’s ability to sustain biodiversity. The collapse of an ecosystem occurs when there is a total loss of the environment’s. Therefore, its typical biodiversity is no longer sustained, which means that a new anthropic ecosystem takes place. The IUCN Red List of Ecosystems (RLE) is a scientific tool that proposes a diagnosis of the current state of ecosystems and the probability of collapsing, meaning the disappearance from nature. The present study evaluated the threat status of 201 terrestrial ecosystems (phytophysiognomies) in the Atlantic Forest, Cerrado and Caatinga biomes. Overall, 137 ecosystems are threatened, of which 13 were classified as "Collapsed", 51 "Critically Endangered", 44 "Endangered" and 29 "Vulnerable". Among the non-threatened, 03 were classified as "Near Threatened" and 61 as "Least Concern". Although threatened ecosystems are a priority for conservation due to their biological importance, their representativeness in Protected Areas is very small. In the Caatinga, protection averages are 3.39% in CR ecosystems, 2.14% in EN and 14.16% in VU; in the Cerrado the averages are 13.32% in the CR, 16.61% in the EN and 6.19% in the VU; in the Atlantic Forest the averages are 14.83% in the CR, 7.14% in the EN and 20.31% in the VU. The average proportion of protected areas in threatened ecosystems is 6.63% in the Caatinga, 13.22% in the Cerrado and 13.42% in the Atlantic Forest. Despite the percentage of Protected Areas being higher in the two Hotspots (Cerrado and Atlantic Forest), many ecosystems are still little or not covered in legally protected territories. Caatinga was classified as the most threatened and least protected biome, among those evaluated in the present study.